Turnover Intention Among Barisa in Coffee Shops - Zidane Muhammad; Paksi, Girindra Mega (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study investigates the phenomenon of turnover intention among baristas working in coffee shops in Malang City, Indonesia. Adopting a qualitative descriptive approach, data were collected through semi-structured interviews with eight baristas employed across seven different coffee shops. The findings highlight four dominant factors influencing turnover intention: work-life balance, compensation, job satisfaction, and employment status. Conflicts between academic and professional responsibilities, limited and inconsistent compensation, as well as the absence of clear career advancement opportunities, were found to heighten turnover intentions. Conversely, intrinsic job satisfaction derived from passion for coffee and customer interaction provided mitigating effects. The study contributes to the literature by offering qualitative insights into turnover intention in the Indonesian context, while also providing practical recommendations for coffee shop managers to reduce turnover.